From Regional Security to Global IR : An Intellectual Journey. - Ayoob, Mohammed. (Lynne Rienner Publishers, 2024)
Mohammed Ayoob's work in the field of international relations, spanning more than four decades, offers invaluable insights into both international conflicts and the security dynamics of the Global South. From Regional Security to Global IR presents a chronological selection of that work from 1989 to 2024, providing a guide to Ayoob's intellectual journey and advancing the concept of Global IR as an inclusive approach to understanding the emerging decentralized world order.